Ultrastructure and cytochemistry of the pearl gland in Piper regnellii (Piperaceae) - da Silva, EMJ; Machado, SR (Nordic Journal of Botany, 1999)
Pearl glands are scattered throughout the lamina of developing leaves and rarely found on adult leaves of Piper regnellii (Piperaceae). The pearl gland is a bicellular secretory trichome composed of a short broad basal cell and a spatula-like, semiglobular apical cell. Four different stages of the pearl grand were determined during its ontogenesis: origin, pre-secretory, secretory and post-secretory. During the pre-secretory stage, mitochondria, ribosomes, dictyosomes, rough endoplasmic reticulum, and plastids with electron dense inclusions were present in the cytoplasm of the apical cell. During the secretory stage, the most remarkable characteristics of the apical cell are the proliferation of dictyosomes and their vesicles, rough endoplasmic reticulum, and modified plastids. At this stage, electron-dense oil drops occur in the plastids as well as scattered within the cytoplasm, proteins and polysaccharides are seen in the plastids, vesicles, and vacuoles. Only polysaccharides are present in the periplasmic space, wall cavities, and on the surface of the apical cell. The polysaccharides are one of the main components of the mucilagenous exudate that covers the developing leaf structures. The apical cell of the senescing trichomes undergoes a progressive degeneration of its cellular components, the plastids being the first organelles to undergo lysis.